Canal surfaces with rational contour curves and blends bypassing the obstacles. (July 2015) - Bizzarri, Michal; Lávička, Miroslav; Vršek, Jan
Abstract: In this paper, we will present an algebraic condition, see(20), which guarantees that a canal surface, given by its rational medial axis transform (MAT), possesses rational generalized contours (i.e., contour curves with respect to a given viewpoint). The remaining computational problem of this approach is how to find the right viewpoint. The canal surfaces fulfilling this distinguished property are suitable for being taken as modeling primitives when some rational approximations of canal surfaces are required. Mainly, we will focus on the low-degree cases such as quadratic and cubic MATs that are especially useful for applications. To document a practical usefulness of the presented approach, we designed and implemented two simple algorithms for computing rational offset blends between two canal surfaces based on the contour method which do not need any further advanced formalism (as e.g. interpolations with MPH curves). A main advantage of the designed blending technique is its simplicity and also an adaptivity to choose a suitable blend satisfying certain constrains (avoiding obstacles, bypassing other objects, etc.). Compared to other similar methods, our approach requires only one SOS decomposition for the whole family of rational canal surfaces sharing the same silhouette, which significantly simplifies the computational complexity. Highlights: The rationality of generalized contours on rational canal surfaces is studied. The contour method is used for computing PN blends between two canal surfaces. The constructed blends can easily satisfy certain constrains, e.g. avoiding obstacles. Only one SOS decomposition for all canal surfaces with the same silhouette is needed.